A novel low-bandgap pyridazine thiadiazole-based conjugated polymer with deep molecular orbital levels. Issue 2 (14th November 2019) - Leventis, A.; Chmovzh, T. N.; Knyazeva, E. A.; Han, Y.; Heeney, M.; Rakitin, O. A.; Bronstein, H.
Abstract : A pyridazine thiadiazole acceptor (PzT) has been utilised in the synthesis of a novel low band-gap D–A copolymer PTTPz. Abstract : A pyridazine thiadiazole acceptor (PzT) has been utilised in the synthesis of a novel low band-gap D–A copolymer PTTPz. It is a much stronger acceptor in comparison to BT and PyT moieties widely incorporated in the literature. Experimental results reveal that per electronegative N atom that is substituted into the acceptor, an effective HOMO and LUMO stabilization energy of ∼0.2–0.1 eV can be achieved.